Recent development of nanoparticles for molecular imaging - Kim, Jonghoon; Lee, Nohyun; Hyeon, Taeghwan (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2017)
Molecular imaging enables us to non-invasively visualize cellular functions and biological processes in living subjects, allowing accurate diagnosis of diseases at early stages. For successful molecular imaging, a suitable contrast agent with high sensitivity is required. To date, various nanoparticles have been developed as contrast agents for medical imaging modalities. In comparison with conventional probes, nanoparticles offer several advantages, including controllable physical properties, facile surface modification and long circulation time. In addition, they can be integrated with various combinations for multimodal imaging and therapy. In this opinion piece, we highlight recent advances and future perspectives of nanomaterials for molecular imaging. This article is part of the themed issue ‘Challenges for chemistry in molecular imaging’.